An investigation of corticospinal tract microstructural integrity in ARSACS using a profilometry MRI analysis: results from the PROSPAX study - Scaravilli, Alessandra; Mari, Gaia; Gabusi, Ilaria; Battocchio, Matteo; Bosticardo, Sara; Schiavi, Simona; Bender, Benjamin; Kessler, Christoph; La Piana, Roberta; van de Warrenburg, Bart P.; Cosottini, Mirco; Timmann, Dagmar; et al. (European journal of neurology, 2025)
Background Spasticity represents a core clinical feature of Autosomal Recessive Spastic Ataxia of Charlevoix-Saguenay (ARSACS) patients. Nonetheless, its pathophysiological substrate is poorly investigated. We assessed the microstructural integrity of the corticospinal tract (CST) using diffusion MRI (dMRI) via profilometry analysis to understand its possible role in the development of spasticity in ARSACS. Materials and Methods In this multi-center prospective study, data of 37 ARSACS (M/F = 21/16; 33.4 ± 12.4 years) and 29 controls (M/F = 13/16; 42.1 ± 17.2 years) acquired within the PROSPAX consortium were collected from January 2021 to October 2022 and analyzed. Differences in terms of global CST microstructural integrity were probed, as well as a possible spatial distribution of the damage along the tract via profilometry analysis. Possible correlations between clinical severity, including the Spastic Paraplegia Rating Scale (SPRS), were also tested. Results A significant global involvement of the CST was found in ARSACS compared to controls (all tests with p < 0.001), with a spatially defined pattern of more pronounced microstructural integrity loss occurring right below and above the pons, a structure that was also confirmed to be thickened in these patients (p < 0.001). A bilateral negative correlation emerged between the microstructural integrity of the CST and clinical indices of spasticity expressed via SPRS (p = 0.02 for both CSTs). Conclusion A clinically meaningful microstructural involvement of CST is present in ARSACS patients, with a spatially defined pattern of damage occurring right below and above a thickened pons. An evaluation of the microstructure of this bundle might serve as a possible biomarker in this condition.